Structure and Development of Financial Institutions and Links with Trust: Cross-Country Evidence - Arturo Galindo; Alberto Chong; César Calderón (Inter-American Development Bank, Research Department, 2001)
We explore the links between trust and a broad range of financial structure and development measures. Our base sample is a cross section of 48 countries and the analysis covers the period 1980-1994. We use a new World Bank data set that provides the most comprehensive coverage of financial development and structure to this date. We find that trust is correlated with financial depth and efficiency as well as with stock market development. Results hold when using an instrumental variable approach, and they are robust to changes in specification when using a formal Sala-i-Martín sensitivity analysis.
Keywords: 330; Vertrauen; Social Capital; Finanzsektor; Aktienmarkt; Schätzung; Welt